The new power eating - Kleiner, Susan M.; Greenwood-Robinson, Maggie (Human Kinetics, Inc., 2019)
Transform your body as you build muscle, lose fat, and maximize performance with The New Power Eating. Author Susan Kleiner delivers the proven strategies she's used with male and female professional athletes and Olympians in one practical, effective resource that gives you the know-how to reach your personal goals. In The New Power Eating, Kleiner brings together the latest scientific research on nutrition planning and explains not just what to eat but also when and how to adjust eating plans for your body and specific energy needs. Whether it's a heavy or light training day, in peak season or off-season, you'll learn how to achieve your physique and performance goals safely, legally, and effectively